Hypericin-functionalized graphene oxide for enhanced mitochondria-targeting and synergistic anticancer effect. (1st September 2018) - Han, Chao; Zhang, Can; Ma, Ting; Zhang, Chao; Luo, Jianguang; Xu, Xiao; Zhao, Huijun; Chen, Yan; Kong, Lingyi
Graphical abstract: Abstract: Effective targeting of mitochondria has emerged as a beneficial strategy in cancer therapy. However, the development of mitochondria-targeting ligands is difficult because of the low permeability of the mitochondrial double membrane. We found that hypericin (HY), a natural product isolated from Hypericum perforatum L., is an effective mitochondria-targeting ligand. HY-functionalized graphene oxide (GO) loaded with doxorubicin (GO-PEG-SS-HY/DOX) increased the synergistic anticancer efficacy of phototherapy and chemotherapy in the absence of apparent adverse side effects. In vitro and in vivo assays suggested GO-PEG-SS-HY/DOX induced the expression of the key proteins of the mitochondria-mediated apoptosis pathway and caused apoptosis of breast carcinoma cells. In addition, GO vehicle exhibited low toxicity toward normal cells, indicating high safety of functionalized GO preparations in antitumor therapy. Therefore, HY-functionalized GO can be successfully used as a platform technology to target mitochondria in cancer cells and improve the therapeutic efficacy of chemotherapeutic drugs. Statement of Significance: Induction of mitochondria-mediated apoptosis is a promising approach in cancer therapy. However, mitochondria are difficult to access and permeate because of their negative membrane potential and highly dense double membrane. Mitochondria-targeting ligands can be conjugated to nanoparticles or small-molecule drugs to enhance their antitumor effect. Here, we showed that the natural photosensitizer hypericin is a novel mitochondria-targeting ligand and that graphene oxide particles co-loaded with hypericin and the chemotherapeutic agent doxorubicin exhibited a synergistic antitumor effect mediated by the mitochondrial-mediated apoptosis. Treatment with such particles in combination with laser irradiation led to apoptosis of the tumor MDA-MB-231 and MCF-7 cells in vitro and in vivo . Furthermore, treatment with hypericin/doxorubicin-functionalized graphene oxide had low cellular toxicity.